Assessment of the knowledge level of a quilombola community in the State of Alagoas about people’s participation in municipal health councils (Research, Society and Development, 2021)
The term remnant of quilombo defines a group of individuals with black descent and who share a religious, cultural, territorial and linguistic legacy, historically characterized by the trajectory of a people who opposed the slavery regime. In the management of the Brazilian Unified Health System, there are Municipal Health Councils, collegiate bodies, which allow users to give their opinion, monitor the execution and oversee health actions, called participation and social control. This study aims to analyze the knowledge of the quilombola community about popular participation in the management of the Unified Health System through the Municipal Health Councils. The methodology used was the quantitative approach of a descriptive nature. Through this study, it was observed that the knowledge of the community about the concept, function, collegiate and its representation in the municipal health councils is precarious. Economic and social factors, in addition to little interest from individuals on health management issues can be triggering factors for this lack of knowledge. It is concluded that there is a need to implement health education strategies aimed at the quilombola community related to rights and duties in health and social control in the management of the SUS, with the aim of bringing greater community involvement in the Municipal Health Councils.